Journey Interrupted: A Phenomenological Exploration of Miscarriage - Marit A. Watson; Vanessa D. Jewell; Sarah Smith (Scholarworks @ WMU, 2018)
Background: Miscarriage is a significant life event that impacts occupational performance, identity, and competence and that influences perceptions of motherhood. Because of the lack of social rituals often attributed to the death of a loved one, miscarriages may result in disenfranchised grief, which impedes coping. Methods: This phenomenological study explored the impact of miscarriage on relationships, perceptions of motherhood, and the meaning of occupation in the context of grief. Data was collected through semi-structured interviews (N = 4) and completion of a brief demographic questionnaire. The interviews were digitally recorded, transcribed verbatim, and reviewed to ensure accuracy. Using inductive thematic analysis, the first author identified initial codes, collated the codes into preliminary themes, and then reviewed, further analyzed, and refined the themes. Results: Three overarching themes were identified: (a) the journey: ambiguity, vulnerability, and the trauma of a miscarriage (b) seeking acknowledgement and validation of loss: impact on relationships; and (c) occupational engagement: evolving roles and perspectives. Conclusion: The findings of this study illustrated the complexity of the lived experience of miscarriage and highlighted the significant impact of miscarriage on self-identify, relationships, and the complex role of occupation in the context of bereavement.